FRACTURES SYSTEMS AND TECTONIC INFLUENCE OF THE SOUTHEAST EDGE OF PARNAÍBA SEDIMENTARY BASIN: SERRA DA CAPIVARA NATIONAL PARK, BRAZIL - Firmino Barbosa, Maria Emanuella; Furrier, Max (Universidade de São Paulo. Faculdade de Filosofia, Letras e Ciências Humanas, 2012)
The Serra da Capivara National Park with their peculiar geomorphological characteristics also make it an important focus of studies, once the refief of the area was the scene of activities done by the pre-historical populations who lived there and who registered the most varied daily activities through rupestral paintings. The geomorphological characteristics of the park are inherited from both a kind of much more humid climate, which lasted until approximately 10 thousand years ago, and from the tectonic activities, whose detailed explanation is far from being understood, for they generated a series of efforts in the sedimentary rocks of the Basin of Parnaíba that resulted in an intriguing system of fractures in various directions, often truncated, of relevant importance for the evolution and current configuration of the relief. The easy visualization of these fractures, through satellite images, aerial photographs, and field work, open a new path for understanding the ruiniform relief, which are common on the southern and south-eastern edges of the park and generated by the tendency of rainwater which percolated these fractures, causing accentuated processes of erosion and sculpting peculiar forms of incredible beauty that fascinate tourists and researchers from various parts of Brazil and the world. The tectonic factor, too often overlooked and underestimated in the configuration of Brazilian relief, begins to emerge so conspicuously in the Brazilian geomorphology community and much of the understanding about patterned produced in the years of 1960 to 1990 are being revised under this new optics.